If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -25 = -5(t + -4) Reorder the terms: -25 = -5(-4 + t) -25 = (-4 * -5 + t * -5) -25 = (20 + -5t) Solving -25 = 20 + -5t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '5t' to each side of the equation. -25 + 5t = 20 + -5t + 5t Combine like terms: -5t + 5t = 0 -25 + 5t = 20 + 0 -25 + 5t = 20 Add '25' to each side of the equation. -25 + 25 + 5t = 20 + 25 Combine like terms: -25 + 25 = 0 0 + 5t = 20 + 25 5t = 20 + 25 Combine like terms: 20 + 25 = 45 5t = 45 Divide each side by '5'. t = 9 Simplifying t = 9
| 4x + 5y - 5z = 28 | | 59-3x=6x+19 | | 4(1+7x)=39-7x | | 3(6x-4)-6=-4x-8 | | 4x-5=115 | | (x-4)x-(x-4)7=0 | | 31-3x=6x+21 | | p^2-7p=0 | | (x-5)+(2x-8)=90 | | x^2-17x=48 | | x-5+2x-8=90 | | 4x^2-17x+41=7x+6 | | 12-9x=56-37x | | 82-6x=11-10x | | (x)(x)(x)=64 | | 4n-7=n+1 | | (x)(x)=75 | | 14=y-17 | | 2g=22 | | x(x)(x)=75 | | X-9x+4x-8x= | | 5x-3=2x-12 | | 5x(5x)(7x)(2x)=75 | | 5x-25= | | 5x-25=3x+5 | | 3w-8/7=w+4 | | 96-12(6-3x)=11x | | 7x(5x)+3x=2x+15 | | 11x+18=8x+14 | | 109-5x=13x+17 | | 6-9x=150-37x | | (4a-3)(5a+5)=8 |